Analysis of eGFR index category and annual eGFR slope association with adverse clinical outcomes using real-world Japanese data: a retrospective database study. Issue 2 (23rd February 2022) - Zhang, Ling; Hauske, Sibylle; Ono, Yasuhisa; Kyaw, Moe H; Steubl, Dominik; Naito, Yusuke; Kanasaki, Keizo
Abstract : Objectives: Real-world clinical outcome data of patients with an above-normal estimated glomerular filtration rate (eGFR) and increasing eGFR over time (eGFR slope) are scarce. Although eGFR is commonly recorded, eGFR slopes are rarely used for adverse outcome risk categorisation in clinical practice. We investigated the association of above-normal/below-normal eGFR ranges and increasing/declining eGFR slopes with clinical outcomes in Japan. Design: Observational cohort study. Setting: Primary and acute care hospitals; 423 centres. Participants: 57 452 patients aged ≥16 years with ≥3 eGFR values (latest available January 2013–December 2016) from the Japanese Medical Data Vision database were stratified into six index eGFR and six eGFR slope groups (slopes calculated using a linear mixed model). Primary and secondary outcome measures: Time-to-event analyses of cardiovascular mortality, all-cause mortality (ACM), all-cause hospitalisation (ACH) and cardiovascular and major kidney events. eGFR and slope groups were analysed by Cox proportional hazard models with multivariable adjustment, using normal eGFR/little-to-no slope groups as reference. Results: Higher risk of clinical outcomes was observed with declining eGFR slope groups versus the reference group; the HR (95% CI) for slope ≤−5 mL/min/1.73 m 2 /year: cardiovascular events 1.8 (1.4 to 2.2), ACH 1.8 (1.5 to 2.1), and ACM 2.8 (1.9 to 4.2) and was non-significant for kidney events 1.5 (0.9 to 2.5). A similar, but non-significant, pattern was observed with increasing slope groups (slope >3 mL/min/1.73 m 2 /year HR (95% CI): cardiovascular events 1.2 (0.9 to 1.5), ACH 1.1 (0.9 to 1.4) and ACM 1.5 (0.9 to 2.3)). Above-normal and below-normal eGFR groups were associated with poorer outcomes versus the reference group, but kidney events were associated with below-normal eGFR only. Conclusion: Poorer clinical outcomes were observed not only for below-normal eGFR and declining eGFR slope groups but also for certain above-normal eGFR and increasing slope groups. eGFR and eGFR slope may, therefore, be useful for identifying patients at high risk of adverse clinical outcomes.